Spreading the word : how customer experience in a traditional retail setting influences consumer traditional and electronic word-of-mouth Intention (2019)
The study of customer experience has gained substantial importance in the consumer behavior field because of how it impacts the development of long-term relationships with customers. The next frontier of customer experience research involves new contexts represented by new channels offered by retailers, thus sparking research interest in the experience lived by customers not only in physical stores but also in virtual stores as a clear representation of the concept of omni-channels. Within this context, consumers’ actions on social media are particularly important because they can act as product or service endorsements to other customers affecting their purchase intentions. In this article, we attempt to bridge the gap between real-world retail experiences and how they connect with the online retail environment through consumer behavior contrasting traditional and eWOM intention at the point of experience immediately after its consumption in a physical setting. In order to do so, a Bayesian hierarchical approach is used to provide an adaptable, low-sample statistical infrastructure for the analysis of the proposed relationships. Our findings show that customer experience in physical stores still have a higher impact on consumer traditional WOM intention than on eWOM intention.